2007
DOI: 10.1186/1741-7007-5-22
|View full text |Cite
|
Sign up to set email alerts
|

Differential affinity of mammalian histone H1 somatic subtypes for DNA and chromatin

Abstract: BackgroundHistone H1 is involved in the formation and maintenance of chromatin higher order structure. H1 has multiple isoforms; the subtypes differ in timing of expression, extent of phosphorylation and turnover rate. In vertebrates, the amino acid substitution rates differ among subtypes by almost one order of magnitude, suggesting that each subtype might have acquired a unique function. We have devised a competitive assay to estimate the relative binding affinities of histone H1 mammalian somatic subtypes H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 68 publications
2
61
0
2
Order By: Relevance
“…Using GFP-labeled proteins, Th'ng et al (12) found histone H1.2 to have lower affinity for chromatin than histone H1.5, whereas histone H1.3 had intermediate binding affinity. In another study, where unlabeled H1 subtypes were used in chromatin competition experiments, H1.2 and H1.5 had lower affinity for chromatin than H1.3 (13). Most likely, differential H1 affinity for chromatin is a result of a combination of phosphorylation and inherent affinity, leading to various distributions of H1 subtypes between the chromosomes and the cytoplasm during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using GFP-labeled proteins, Th'ng et al (12) found histone H1.2 to have lower affinity for chromatin than histone H1.5, whereas histone H1.3 had intermediate binding affinity. In another study, where unlabeled H1 subtypes were used in chromatin competition experiments, H1.2 and H1.5 had lower affinity for chromatin than H1.3 (13). Most likely, differential H1 affinity for chromatin is a result of a combination of phosphorylation and inherent affinity, leading to various distributions of H1 subtypes between the chromosomes and the cytoplasm during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although there seems to be a noteworthy redundancy among the histone H1 subtypes (10), evolutionary data indicate that they posses different functional roles (11). They differ in affinity for chromatin (12,13), ability to affect gene regulation (14), and are found to localize to different parts of the nuclei (12). Thus, GFP-labeled H1.1, H1.2, and H1.3 were mainly found in euchromatin, whereas H1.4 and H1.5 were more common in heterochromatin (12).…”
mentioning
confidence: 99%
“…H1 isotypes isolated from rat brains were classified as possessing high (H1e, H1 0 , and H1d), intermediate (H1c and H1b), and low binding affinities (H1a) (38). No appreciable differences in the binding affinities between human H1 isotypes H1-0 and H1.2 (the paralog of mouse H1c) were found in in vitro assays (39), although these isotypes were reported to have different binding characteristics by in vivo experiments (40).…”
Section: Discussionmentioning
confidence: 99%
“…Las histonas H1 difieren en estabilidad evolutiva (10) y en las tasas relativas de síntesis y degradación, en células en división y en células quiescentes, propiedades que permiten cambios en sus proporciones relativas durante el desarrollo y la maduración de los tejidos. Las histonas H1 presentan diferencias de afinidad relativa por el ADN y por la cromatina; la H1a es el subtipo con más baja afinidad, las H1b y H1c tienen afinidades intermedias y las H1d, H1e y H1° tienen las afinidades más altas (11).…”
Section: Introductionunclassified